Correlation between standard deviation of red blood cell distribution width，platelet/lymphocyte ratio and left ventricular hypertrophy in patients with diabetic kidney disease - Shang Shi-li; Chen Jing-shan; Sun Zi-juan; Bi Li-na; Luo Sha; Li Jun (Linchuang shenzangbing zazhi)
ObjectiveTo explore the potential relationship between standard deviation of red blood cell distribution width （RDW-SD），platelet/lymphocyte ratio （PLR） and left ventricular hypertrophy （LVH） in patients with diabetic kidney disease （DKD）.MethodsA total of 236 patients fulfilling the clinical diagnostic criteria of DKD were selected as research subjects. The changes of heart structure were detected by color Doppler ultrasound. According to the diagnostic criteria of LVH，they were divided into two groups of non-LVH （n=125） and LVH （n=111）. Demographic data and the relevant clinical laboratory parameters of two groups were compared. Spearman’s correlation and multivariate Logistic regression were employed for examining the risk factors of DKD patients complicated with LVH，And receiver operating curve （ROC） was plotted for analyzing the predictive value of RDW-SD or PLR for LVH in DKD patients.ResultsCorrelation results indicated that serum phosphorus，uric acid，RDW-SD and PLR were positively correlated with left ventricular mass index （LVMI） （r=0.187，0.149，0.332，0.445，P<0.05）；lymphocyte absolute value，total protein，triglyceride，serum calcium and glomerular filtration rate were negatively correlated with LVMI （r=-0.377，-0.175，-0.234，-0.245，-0.358，P<0.01）.Regression analysis showed that RDW-SD>44% and PLR （per10） were independent risk factors for DKD patients with LVH. OR values were 2.417 （95%CI 1.356-4.308，P=0.003） and 1.190 （95%CI 1.117~1.268，P<0.01）. ROC curve indicated that RDW-SD，PLR，RDW-SD plus PLR were the predictors of LVH in DKD patients （P<0.05） and the area under the curve （AUC） were 0.777，0.804 and 0.826 respectively.ConclusionsElevations of RDW-SD and PLR are significantly correlated with LVH and the combination of two parameters can predict the risk of LVH in DKD patients. Therefore dynamic monitoring of RDW-SD and PLR offers clinical guidance for preventing adverse cardiovascular events.